2021
DOI: 10.3389/fpubh.2021.550860
|View full text |Cite
|
Sign up to set email alerts
|

Normal Gestational Weight Gain Protects From Large-for-Gestational-Age Birth Among Women With Obesity and Gestational Diabetes

Abstract: Background: Pre-pregnancy obesity, excess gestational weight gain (GWG), and gestational diabetes (GDM) increase fetal growth. Our aim was to assess whether normal GWG is associated with lower risk for a large-for-gestational-age (LGA; over the 90th percentile of birth weight for sex and gestational age) infant and lower birth weight standard deviation (SD) score in the presence of GDM and maternal obesity.Methods: This multicenter case-control study is part of the Finnish Gestational Diabetes (FinnGeDi) Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
4
15
0
2
Order By: Relevance
“…Excessive GWG during periods 12-33 weeks and 12 weeks to delivery increased the risk of LGA and while insufficient GWG during periods 12-33 weeks, 12 weeks to delivery and 33 weeks to delivery week reduced the risk of LGA. These findings confirm previous studies which have indicated similar effects of excessive GWG on LGA [37][38][39][40][41]. Drehmer et al [42] reported that LGA was linked with excessive weight gain in the second trimester which is consistent with the results of our study [38].…”
Section: Discussionsupporting
confidence: 93%
“…Excessive GWG during periods 12-33 weeks and 12 weeks to delivery increased the risk of LGA and while insufficient GWG during periods 12-33 weeks, 12 weeks to delivery and 33 weeks to delivery week reduced the risk of LGA. These findings confirm previous studies which have indicated similar effects of excessive GWG on LGA [37][38][39][40][41]. Drehmer et al [42] reported that LGA was linked with excessive weight gain in the second trimester which is consistent with the results of our study [38].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this cross-sectional study show a high prevalence of inadequate GWG, as measured by IOM criteria, among adult Brazilian women diagnosed with GDM. Our findings point to a higher chance of newborn prematurity among women with insufficient GWG, and a higher chance of HDP and LGA infants among the women with excessive GWG, which is consistent with previous scientific evidence [11,18]. In a meta-analysis of studies of the North American and European population, any adverse outcome, including HDP, GDM, cesarean section, premature birth, SGA or LGA newborns, was observed in 37.2% of the 200,000 women included, ranging from 34.7% in the women who had pre- pregnancy underweight, to 61% in the women with grade 3 obesity before pregnancy [19].…”
Section: Discussionsupporting
confidence: 92%
“…According to a study conducted with 832 nulliparous women with GDM in China, similar results to the present study were found [21], as was observed in a multicenter caseecontrol study from Finland [18]. Excessive GWG was associated with pre-gestational obesity and also with an increased incidence of macrosomia and cesarean delivery [18,22,23]. It is fundamental to propose interventions aimed at achieving normal GWG that have the power to reduce the occurrence of LGA and birth weight SD scores, even in situations where GDM and obesity are present [18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations